Thermodynamical parameters of phase transitions in model lipid membranes as a marker of membranotropic effects of antibiotics in generic drugs - Krasnikova, A. O.; Vashchenko, O. V.; Kasian, N. A.; Iermak, Iu. L.; Markevich, M. A. (Biophysical Bulletin)
Mulitbilayer membranes of L-α-dipalmitoyl phospatidylcholine (DPPC) containing antibiotics were examined by means of differential scanning calorimetry (DSC). The antibiotics, amoxicillin and azithromycin, were represented by two groups of generic drugs. Phase transitions parameters of DPPC membranes obtained by DSC revealed to be different within each group and between them. For azithromycin, concentration dependences of basic thermodynamic parameters demonstrated certain distinctions depending on the specific drug. The effects observed could be interpreted as interference of membranotropic action of the antibiotic and excipients.